Riding with the king - Roach, Lisa; Ireland, Daphne (Australia : Mission Films, 1989)
This video captures the spirit and charm of the legacy of Elvis Presley by accompanying a fan through Elvis country, from Tupelo, Mississippi to Memphis, Tennessee. It visits his birthplace and other shrines of Presleydom, and meets people who were associated with Elvis plus his adoring fans and impersonators
Title from title screen
DVD format
Keywords: Presley, Elvis, 1935-1977; Rock musicians -- United States; Singers